Crowdsourcing 3D cultural heritage: best practice for mass photogrammetry. Issue 1 (4th February 2019) - Ch'ng, Eugene; Cai, Shengdan; Zhang, Tong Evelyn; Leow, Fui-Theng
Abstract : Purpose: The purpose of this paper is to present the rationale for democratising the digital reproduction of cultural heritage via "mass photogrammetry", by providing approaches to digitise objects from cultural heritage collections housed in museums or private spaces using devices and photogrammetry techniques accessible to the public. The paper is intended as a democratised approach rather than as a "scientific approach" for the purpose that mass photogrammetry can be achieved at scale. Design/methodology/approach: The methodology aims to convert the art of photogrammetry into a more mechanical approach by overcoming common difficulties faced within exhibition spaces. This approach is replicable and allows anyone possessing inexpensive equipment with basic knowledge of photogrammetry to achieve acceptable results. Findings: The authors present the experience of acquiring over 300 3D models through photogrammetry from over 25 priority sites and museums in East Asia. The approach covers the entire process from capturing to editing, and importing 3D models into integrated development environments for displays such as interactive 3D, Virtual Reality and Augmented Reality. Practical implications: The simplistic approach for democratised, mass photogrammetry has implications for stirring public interests in the digital preservation of heritage objects in countries where museums and cultural institutions have little access to digital teams, provided that Intellectual Property issues are cared for. The approach to mass photogrammetry also means that personal cultural heritage objects hidden within the homes of various societies and relics in circulation in the antiques market can be made accessible globally at scale. Originality/value: This paper focuses on the complete practical nature of photogrammetry conducted within cultural institutions. The authors provide a means for the public to conduct good photogrammetry so that all cultural heritage objects can be digitally recorded and shared globally so as to promote the cross-cultural appreciation of material cultures from the past.